2001
DOI: 10.1007/s001340000822
|View full text |Cite
|
Sign up to set email alerts
|

Current management and outcome of tracheobronchial malacia and stenosis presenting to the paediatric intensive care unit

Abstract: Length of ventilation and bronchographic diagnosis did not predict survival. The only factor found to contribute significantly to mortality was the presence of complex cardiac and/or syndromic pathology. However, patients with stenosis required longer ventilatory support than patients with malacia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Its management can be very challenging. Three strategies can be employed, as we have described elsewhere [38] in the management of conventional tracheo-bronchomalacia. Prolonged ventilatory support with CPAP may work, but a few patients have required tracheostomy and 'home' BIPAP support for up to 2 years.…”
Section: Those Related To Repair Of Associated Lesions Andmentioning
confidence: 99%
“…Its management can be very challenging. Three strategies can be employed, as we have described elsewhere [38] in the management of conventional tracheo-bronchomalacia. Prolonged ventilatory support with CPAP may work, but a few patients have required tracheostomy and 'home' BIPAP support for up to 2 years.…”
Section: Those Related To Repair Of Associated Lesions Andmentioning
confidence: 99%
“…The mechanisms include anomalous relationships between the tracheobronchial tree and vascular structures (complete or partial vascular rings) or result from extrinsic compression caused by dilated great vessels, left atrial enlargement, massive cardiomegaly, or postoperative reconstructed aortic arches [7]. Survival outcome analysis among patients showed that patients with cardiac/syndromic anomalies had inferior survival compared to patients with primary airway stenosis [6]. In this situation, flexible bronchoscopy is necessary to identify complete tracheal rings, the severity of stenosis, and any dynamic collapse of the airway [2].…”
Section: Discussionmentioning
confidence: 98%
“…Figure 9 shows the Kaplan–Meier curve of survival in different diagnostic groups. We found that associated comorbidity was more predictive of mortality, and patients with cardiac problems or who were syndromic had a much poorer outcome than patients who had tracheomalacia associated with trachea-esophageal fistula, as an isolated primary airway problem or from prematurity (44). …”
Section: Prognosismentioning
confidence: 90%